New arenas of inclusion: experiences of individuals with intellectual disability employed in higher education - Ramsdal, Gro H.; Mevold, Silje; Johansen, Leif Inge; Wynn, Rolf (Frontiers in Psychiatry, 2025)
IntroductionPrior studies have found that people with intellectual disabilities (ID) often experience being excluded from important parts of society, and unemployment and lack of social connections may severely negatively impact quality of life for people with ID.MethodsFive persons with ID participating in a project at a Norwegian University were interviewed, with a particular emphasis on how they experienced social inclusion at this non-sheltered work environment. The participants also worked in a sheltered environment. The data analysis was performed in accordance with the method of thematic analysis.ResultsThree main themes that emerged from the data: 1) ‘Experienced employees’, indicating that the participants had worked in different types of jobs and evaluated their current work positively in light of prior work experiences; 2) ‘Suitable work challenges’, implying that the participants described having had some influence over their work and were generally satisfied with their assignments; 3) ‘Social belonging’, demonstrating how the participants underlined the importance of meeting new people, expanding their network and being appreciated at work.DiscussionThe participants were generally satisfied with work at the University, and reported feeling included through the forming of relationships with other people at the workplace. However, they also emphasised the importance of their work in a sheltered environment, where they felt secure and had friends.ConclusionThe participant described experiences of belonging and being included when at work at the University. A combination of sheltered and non-sheltered work seemed to be experienced positively by the participants.